Kajian Estetika Desain Batik Khas Mojokerto â€œSurya Citra Majapahitâ€ - Irfa'ina Rohana Salma (Institut Seni Indonesia Surakarta, 2012)
Batik as national pride is a valuable art that developed in these regions. Batik as identity of the local arts and culture also have potential as a creative industry that is able to improve the welfare of the craftsmen. This potential is what prompted many local governments trying to revive the art of batik potential in the region. The government of Mojokerto in 2012 held Batik Design Competition which produced some designs as the winner, which are then used as typical motif of the region. Aesthetic assessment of batik design winning competition aims to determine the winner of the content of its values of beauty and uniqueness. The methods employed in the literature study approach. The study focused on a favorite winning competitian have taken title: